Local history as a means of activating the creative potential of history students - Kashaba, O.; Shcherbyna І. (Problems of Engineer-Pedagogical Education, 2021)
itting cultural values, norms, ideals, forms of reproduction of the national-cultural world, and promote the formation of interethnic tolerant relations. Local history as a component of humanitarian historical education contributes to the activation of the creative potential of students, opens diverse opportunities for them, creates conditions for personal and social interests, and cultivates civic competencies. The authors of the article make an attempt to summarize the existing experience of domestic local history studies, to analyze the main directions of studies and research methods, as well as to reveal the possibilities of local history in the process of activating the creative potential of students, especially students of history. While training future specialists in history, the disciplines of local history play a significant role. Their implementation is not only one of the stages of theoretical training of students, but also the result of practical orientation when preparing for practical classes, while doing independent creative activity, individual, and research work, as well as during students’ industrial and pedagogical internships. The discipline "Local history" plays a crucial role in this process. The study of the history of the native land is transformed from a methodological approach into a general pedagogical principle and creates a basis for the formation of deep professional knowledge, historical thinking, promotes creative understanding of the experience gained by local historians from different regions of Ukraine. The use of local history materials in teaching historical disciplines and practical application of the acquired knowledge about the native land provide ample opportunities to increase the interest of history students in the cultural and historical heritage of the Ukrainian people, activate their creative potential, broaden the worldview and enhance the national dignity of the young.